694. Unexpected Diversity of Rotavirus Genotypes in Pediatric Population. (31st December 2020) - Koukou, Dimitra; Chatzichristou, Panagiota; Tatsi, Elizabeth-Barbara; Liakopoulou, Theodota; Chronopoulou, Genovepha; Michos, Athanasios; Syriopoulou, Vassiliki
Abstract: Background: Rotavirus (RV) is the leading cause of viral gastroenteritis in children. Although RV genotypes differ geographically and temporally, five are the predominant genotypes circulating worldwide. Aim of our study was to monitor possible changes in distribution of Rotavirus genotypes circulating in Greek pediatric population during the post vaccine era. Methods: Demographic data and fecal samples were collected from children ≤15 years old with symptoms of acute gastroenteritis who visited emergency units of Pediatric Hospitals in Greece from September 2016 to August 2019. Samples were tested for RV Group A antigen with rapid immunochromatographic assay. Positive samples were further G and P typed employing RT-PCR, semi-nested multiplex PCR and Sanger sequencing of the VP7 and VP4 genes. Results: A total of 660 children participated in the study with median age 31±29 months. Males outnumbered females (59%). Most of them lived in urban cities (85%). RV genotyping distribution was G4P[8] (41%), G1P[8] (22%), G2P[4] (14%), G9P[8] (8%), G9P[4] (5, 5%), G12P[8] (2%) and G3P[8] (1, 8%). Unusual and mixed genotypes were identified in 3, 2% and 2, 5% of the samples respectively. During 2016-2017 and 2017-2018, G4P[8] was the predominant genotype in 67% and 51% of the annual samples. However, in 2018-2019 the most common genotypes were G9P[8] and G9P[4] (33% in total) followed by G2P[4] (27%). Interestingly, the genotype G9P[4] was not detected at all in the first two years of the study. Conclusion: This study indicates diversity of the predominant RV genotypes in Greek children during 2016-2019. The emergence of G9 as the most common genotype as well as the significant detection of uncommon ones highlight the importance of continuous surveillance of RV genotyping during the post vaccine period. Disclosures: All Authors : No reported disclosures